2014
DOI: 10.1063/1.4871282
|View full text |Cite
|
Sign up to set email alerts
|

Trapping helium in Y2Ti2O7 compared to in matrix iron: A first principles study

Abstract: Pyrochlore Y2Ti2O7 is a primary precipitate phase in nano-structured ferritic alloys (NFAs) for fission and fusion energy applications. We report a theoretical study for assessing the relative stability of trapping helium in Y2Ti2O7 versus in matrix iron. Various defect structures and the associated energies are examined and compared. Results reveal that helium can be deeply trapped in Y2Ti2O7 and that the corresponding self-interaction is essentially repulsive. Transmutant helium in NFAs prefers to occupy ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 49 publications
4
35
0
Order By: Relevance
“…Once oxide-attached helium bubble grows larger than critical radius, the corresponding helium energy in bubble would be lower than in oxide [23]. Until then, helium atoms started to flow from internal of oxide to oxide-attached helium bubble and subsequently form to a larger bubble [23,36]. Thus, it could imagine that the final size of the bubble strongly depends on the size and number density of oxides.…”
Section: Evolution Of Microstructure and Helium Distribution In He Iomentioning
confidence: 95%
See 2 more Smart Citations
“…Once oxide-attached helium bubble grows larger than critical radius, the corresponding helium energy in bubble would be lower than in oxide [23]. Until then, helium atoms started to flow from internal of oxide to oxide-attached helium bubble and subsequently form to a larger bubble [23,36]. Thus, it could imagine that the final size of the bubble strongly depends on the size and number density of oxides.…”
Section: Evolution Of Microstructure and Helium Distribution In He Iomentioning
confidence: 95%
“…It showed that helium atoms are more easily trapped at Y 2 Ti 2 O 7 oxide octahedral interstitial sites than FeeCr matrix sites due to lower corresponding energy (~0.94 eV/atom in Y 2 Ti 2 O 7 ,~2.34 eV/atom in matrix) [36]. At the beginning of helium implantation, initial helium could be deeply trapped inside the oxide.…”
Section: Evolution Of Microstructure and Helium Distribution In He Iomentioning
confidence: 98%
See 1 more Smart Citation
“…Generally speaking, there exist plenty of vacancy defects in Fe host materials when subjected to irradiation, and He atoms tend to consume individual vacancy sites in Fe as much as possible [39]. In our previous work, we have already studied the vacancy effects on He behaviors including the vacancy-He interaction and vacancy trapping for multiple He atom in bcc Fe [12].…”
Section: He Formation Energy In Presence Of Cr and Wmentioning
confidence: 99%
“…25,17) and in iron 25,26 in Table II. We note that the most energetically favored site for helium in Y 2 TiO 5 is the open channel site (Type C), with E f ¼ 0.62 eV/atom.…”
Section: B Helium In Y 2 Tio 5 and Helium Partition In Nfasmentioning
confidence: 99%